2012
DOI: 10.1111/1462-2920.12024
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivotranscriptional profiling reveals a common set of genes important for the adaptation ofPseudomonas aeruginosato chronically infected host sites

Abstract: The opportunistic bacterium Pseudomonas aeruginosa is a major nosocomial pathogen causing both devastating acute and chronic persistent infections. During the course of an infection, P.  aeruginosa rapidly adapts to the specific conditions within the host. In the present study, we aimed at the identification of genes that are highly expressed during biofilm infections such as in chronically infected lungs of patients with cystic fibrosis (CF), burn wounds and subcutaneous mouse tumours. We found a common subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 57 publications
2
45
0
Order By: Relevance
“…Second, the niche within the tumor largely reflects environmental characteristics of the chronically infected CF respiratory tract. The in vivo transcription profile of wild-type P. aeruginosa isolated from tumors was previously shown to match that of isolates from CF lungs and lesions of patients suffering from burn wounds (21). This provides evidence that the microenvironments of colonized solid tumors and CF lungs or burn wounds are very similar.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Second, the niche within the tumor largely reflects environmental characteristics of the chronically infected CF respiratory tract. The in vivo transcription profile of wild-type P. aeruginosa isolated from tumors was previously shown to match that of isolates from CF lungs and lesions of patients suffering from burn wounds (21). This provides evidence that the microenvironments of colonized solid tumors and CF lungs or burn wounds are very similar.…”
Section: Discussionmentioning
confidence: 56%
“…The microenvironment of the colonized tumor leads to biofilm formation by the bacteria (18)(19)(20). Apparently, this microenvironment of the murine tumor resembles very closely that found in the CF lung or in burn wounds (21).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…To our knowledge, this is the first report linking the catabolism of host-derived substrates and increased Anr activity under conditions where Anr is thought to be largely inactive because of the presence of oxygen (17,55). A recent study has shown that P. aeruginosa betI and betB transcripts were particularly upregulated in CF patient lung infections, as well as burn wound samples, compared to those in planktonic controls (56). Because the betaine aldehyde dehydrogenase-encoding genes are responsible for the conversion of choline to GB (57), this implies choline uptake and utilization in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, we could show that Salmonella enterica serovar Typhimurium, as well as P. aeruginosa, forms biofilms in this neoplastic tissue (32). Transcriptional profiling of tumor-colonizing P. aeruginosa revealed that the microenvironment encountered by the bacteria in the tumor closely resembles the microenvironment of the CF lung (33). Using this model, we set out to investigate species-dependent phenotypic and transcriptomic changes during in vivo coinfections by V. parvula and P. aeruginosa.…”
mentioning
confidence: 99%